ITSM Tasks in Digital Transformation Process - Jana FILANOVÁ; Anna HAMRANOVÁ; Anikó TÖRÖKOVÁ (Communications of International Proceedings, 2021)
The paper deals with the issue of digital transformation of companies in relation to the management of enterprise IS/IT based on services. Specifically, it is a specification of business areas important in the digital transformation of businesses and the design of a model of tasks that need to be addressed within the IT Service Management (ITSM) in each specified area. The paper uses standard methods of scientific work, including analysis, synthesis, comparison and selection. The result is a “Model of ITSM tasks in digital transformation”, which identifies the main tasks of ITSM in each area of digital transformation. These areas are: digital business strategy, implementation of pilot projects, knowledge and skills, data analysis, business process innovation and ecosystem digital access. The designed model can help companies navigate themselves in the issue of digital transformation, it can prepare them for all areas that will have to be addressed in the process of digital transformation. The model is not a final static solution, but it is a dynamically evolving process in line with the development of information technology.
Keywords: Industry 4.0; Digital Transformation; IT Service Management; ITIL.